METODE PENGEMBANGAN MANAJEMEN PENDIDIKAN ISLAM DI SMP IT BINA INSAN BATANG KUIS - Iman, Mujhirul (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2024)
Islamic education management is a system used to organize and provide learning-teaching processes based on the principles of Islamic religion. The study of Islamic education management aims to improve students' understanding of the management of education in institutions in particular in education and society as a whole. The purpose of this research is to discern about the development of Islamic education management in particular in the Bina Insan IT High School. This research method uses a qualitative method with data collection through a direct interview with the head of the school. In conclusion, Islamic education needs to adapt technology wisely, adapt to the challenges of globalization, and strengthen the holistic aspect of education. The development of an effective Islamic educational institution requires good management, involving proper planning, organization, guidance, and control. Leaders of Islamic education must be able to adapt to change and keep up with technological and scientific developments.